Pernikahan Usia Dini dan Perceraian: Menyibak Fenomena yang Sering Diabaikan di Era Modern - Ariz Rizaludin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Early marriage is still a significant issue in the modern era, especially in Tasikmalaya Regency, although various efforts have been made to overcome this phenomenon. This research aims to analyze the factors that influence early marriage and its impact on the divorce of young couples, especially in the local social, cultural and economic context. Using descriptive qualitative research methods, data was collected through in-depth interviews with young couples, community leaders, and the Religious Courts, and supported by quantitative data from official documents related to divorce cases. The research results show that the main factors that encourage early marriage are social pressure from the family and environment, cultural norms that consider early marriage as a tradition, and unstable family economic conditions. The emotional and financial unpreparedness of young couples is the main cause of the high divorce rate in this group. Apart from that, divorce has an impact on social and psychological stability, especially on children born from the marriage. The implications of this research highlight the importance of educating the public regarding the risks of early marriage as well as strengthening regulations and mentoring programs for young couples. Synergy is needed between the government, religious institutions and local communities to create comprehensive interventions to prevent early marriage and reduce its impact. It is hoped that this research can become the basis for formulating policies and programs that are more effective in dealing with early marriage and divorce in the future.